PENGUATAN PENGETAHUAN DETEKSI DINI KANKER PAYUDARA MELALUI GERAKAN SADARI PADA SISWI KELAS 3 SMPN 2 KERAMBITAN - Evvy Anjar Puspitasari; Ika Sumiyarsi Sukamto (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2026)
This community service aimed to assess the effectiveness of SADARI education in increasing knowledge of early breast cancer detection among 9th-grade female students at SMP Negeri 2 Kerambitan. The activity used a quasi-experimental approach with a one-group pre-test and post-test design involving 76 participants. Educational interventions were conducted through interactive lectures and live demonstrations explaining the concept, purpose, procedure, and benefits of SADARI. The results showed a significant improvement in students’ knowledge after the intervention. Before education, 82.43% had good knowledge, increasing to 94.59% afterward. This indicates that SADARI education effectively enhances students’ understanding and awareness of breast cancer prevention. It is recommended that schools routinely integrate SADARI education into adolescent reproductive health programs.